Neuropathological correlates of structural and functional imaging biomarkers in 4-repeat tauopathies - Spina, Salvatore; Brown, Jesse A; Deng, Jersey; Gardner, Raquel C; Nana, Alissa L; Hwang, Ji-Hye L; Gaus, Stephanie E; Huang, Eric J; Kramer, Joel H; Rosen, Howie J; Kornak, John; Neuhaus, John; et al. (Brain (London, England : 1878), 2019)
Neurodegenerative dementia syndromes are characterized by spreading of pathological protein deposition along syndrome-specific neural networks. Structural and functional MRI measures can assess the integrity of these networks and have been proposed as biomarkers of disease progression for clinical trials. The relationship between in vivo imaging measures and pathological features, at the single subject level, remains largely unknown. Patient-specific maps of atrophy and seed-based intrinsic connectivity disruption, as compared to normal controls, were obtained for 27 patients subsequently diagnosed with progressive supranuclear palsy (n = 16, seven males, age at death 68.9 ± 6.0 years, imaging-to-pathology interval = 670.2 ± 425.1 days) or corticobasal degeneration (n = 11, two males, age at death 66.7 ± 5.4 years, imaging-to-pathology interval = 696.2 ± 482.2 days). A linear mixed effect model with crossed random effects was used to test regional and single-subject level associations between post-mortem regional measures of neurodegeneration and tau inclusion burden, on the one hand, and regional volume loss and seed-based intrinsic connectivity reduction, on the other. A significant association was found between tau inclusion burden and in vivo volume loss, at the regional level and independent of neurodegeneration severity, in both progressive supranuclear palsy [n = 340 regions; beta 0.036; 95% confidence interval (CI): 0.001, 0.072; P = 0.046] and corticobasal degeneration (n = 215 regions; beta 0.044; 95% CI: 0.009, 0.079; P = 0.013). We also found a significant association between post-mortem neurodegeneration and in vivo volume loss in both progressive supranuclear palsy (n = 340 regions; beta 0.155; 95% CI: 0.061, 0.248; P = 0.001) and corticobasal degeneration (n = 215 regions; beta 0.277; 95% CI: 0.104, 0.450; P = 0.002). We found a significant association between regional neurodegeneration and intrinsic connectivity dysfunction in corticobasal degeneration (n = 215 regions; beta 0.074; 95% CI: 0.005, 0.143; P = 0.035), but no other associations between post-mortem measures of tauopathy and intrinsic connectivity dysfunction reached statistical significance. Our data suggest that in vivo structural imaging measures reflect independent contributions from neurodegeneration and tau burden in progressive supranuclear palsy and corticobasal degeneration. Seed-based measures of intrinsic connectivity dysfunction showed less reliable predictive value when used as in vivo biomarkers of tauopathy. The findings provide important guidance for the use of imaging biomarkers as indirect in vivo assays of microscopic pathology.